VD_FINDINFO HC / 2014 / 351 vom 7. April 2014 - VD Tribunal cantonal (2014)
TRANSACTION JUDICIAIRE, RÉVISIONDÉCISION, CRAINTE FONDÉE, OBLIGATION D'ENTRETIEN | 176 al. 1 ch. 1 CC, 29 CO, 328 al. 1 let. c CPC (CH)